2017
DOI: 10.1016/j.tca.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of MgSO4 – H2O system dehydration at low pressure in view of heat storage

Abstract: Study about magnesium sulfatewater vapor equilibrium proved to be very interesting especially on the use of dehydration-hydration reactions for the heat storage application in recent research. Heat is realized by hydration of lower hydrates as this reaction is exothermic. Therefore, reversible reaction, endothermic thermal dehydration of higher hydrates, is used for charging of system and in this state the energy can be stored over long time. Even if magnesium sulfate appears as promising candidate with high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…The quite slow kinetics could be due to the transition from the amorphous phase (stable in dehydrated conditions, reported in XRD patterns in Figure 3) to the crystalline phase (salt hydrate), which takes place during the hydration process. Nevertheless, the hydration/dehydration of magnesium sulfate hexahydrate depends on both temperature and water vapor pressure showing that the equilibrium between water vapor and the salt is bivariant [11].…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…The quite slow kinetics could be due to the transition from the amorphous phase (stable in dehydrated conditions, reported in XRD patterns in Figure 3) to the crystalline phase (salt hydrate), which takes place during the hydration process. Nevertheless, the hydration/dehydration of magnesium sulfate hexahydrate depends on both temperature and water vapor pressure showing that the equilibrium between water vapor and the salt is bivariant [11].…”
Section: mentioning
confidence: 99%
“…Several combinations of salt hydrates and matrices for thermal energy storage exist. One of the salts that have been extensively evaluated in the scientific literature is MgSO 4 •7H 2 O, whose theoretical energy storage density is 2.8 GJ/m 3 [11] and can be used under both ambient pressure and sub-atmospheric pressure [12], thus being suitable for the application in open cycles or closed cycles. The salt can be efficiently regenerated also at temperatures < 150 • C, compatible with the integration in low-grade heat recovery systems or solar systems in buildings [13].…”
Section: Introductionmentioning
confidence: 99%
“…That is, the crystalline water content of the compounds could vary continuously with temperature and water vapor pressure without any change in their crystalline system (e.g., this effect was recently observed for MgSO % hydrates.) 20 Discussions about the accuracy of this interpretation of the CaSO % -H + O system is found in several works as, for instance, the reviews presented by Posnjak 21 or Ramsdell and Partridge 22 . We can also find the works from Gardet et al 23 and Soustelle et al 24 that reported calcium sulfate hydrates of the form CaSO % ⋅ εH + O for which the water content would vary in the interval 0 ≤ ε ≤ 0.67 depending on two intensive parameters: temperature and water vapor pressure.…”
Section: Introductionmentioning
confidence: 96%
“…When the shift from ideal behavior is not large, it is reasonable to consider the approximation of regular solutions. Hence, the activity coefficients of each component of the surface solution can be expressed by the second-order Margules activity model as follows 4,8,9 ln γ G = B(T)x GH , = B(T)θ ,…”
Section: Thermodynamic Modelsmentioning
confidence: 99%